Comparison of Ziehl-Neelsen Microscopy Technique and Genexpert in the Diagnosis of Tuberculosis in Sudanese Patients - Ali Mohammedain Ali, Mubarak S Elkarsany, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The quality of tuberculosis diagnosis service is indispensable for early infection control and preventing unnecessary anti-tubercular therapy use. TB diagnosis in Sudan mainly relies on detecting tubercule bacilli using the Ziehl-Neelsen (ZN) staining technique. Thus, the current study aimed to compare the ZN microscopy with GeneXpert in diagnosing pulmonary tuberculosis (PTB) in TB laboratories center in Khartoum state, Sudan. Methods: A cross-sectional study was carried out at the TB laboratories diagnosis center in Khartoum state from April 2019 to January 2020. A total of 183 sputum samples were processed and examined by the Ziel-Neelsen (ZN) technique and GeneXpert assay for the detection of tubercle bacilli. Results: Out of 183 sputum samples analyzed, 80.9% were AFB smear-positive, of which 65.6% were male patients. Most patients (57.4%) were within the age group of 20 – 39 years old. All smear-positive samples were detected positive for Mycobacterium tuberculosis by GeneXpert. However, one case of smear-positive PTB was given a negative result by GeneXpert. These results demonstrate that GeneXpert is crucial for confirming TB cases to control TB infection and avoid unnecessary anti-tubercular drug use. Conclusion: ZN microscopy can result in false positivity, which may lead to the misuse of anti-tuberculosis drugs. A positive test should also be confirmed by the GeneXpert and culture techniques. Keywords: Mycobacterium tuberculosis, Tuberculosis, GeneXpert, Ziel-Neelsen stain